2012
DOI: 10.1016/j.chroma.2012.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Separation and quantification of microalgal carbohydrates

Abstract: Structural carbohydrates can constitute a large fraction of the dry weight of algal biomass and thus accurate identification and quantification is important for summative mass closure. Two limitations to the accurate characterization of microalgal carbohydrates are the lack of a robust analytical procedure to hydrolyze polymeric carbohydrates to their respective monomers and the subsequent identification and quantification of those monosaccharides. We address the second limitation, chromatographic separation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 40 publications
6
94
1
2
Order By: Relevance
“…However, establishing the relationship between the chemical structure of the polysaccharides and their biological activity is not an easy task due to the huge complexity of microalgal carbohydrates, characterized by highly branched heteropolymers with a high diversity in their monosaccharide composition and distribution as well as in their glycoside bonds [30,33]. Therefore, the exhaustive characterization of microalgal carbohydrates presents some analytical limitations making more complex their analysis as the size of the carbohydrates increases [29]. Regarding the extraction of these compounds, the great majority of the applications consist of a concentration step using low temperatures followed by precipitation with a variety of organic solvents.…”
Section: Extraction Of Carbohydrates From Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…However, establishing the relationship between the chemical structure of the polysaccharides and their biological activity is not an easy task due to the huge complexity of microalgal carbohydrates, characterized by highly branched heteropolymers with a high diversity in their monosaccharide composition and distribution as well as in their glycoside bonds [30,33]. Therefore, the exhaustive characterization of microalgal carbohydrates presents some analytical limitations making more complex their analysis as the size of the carbohydrates increases [29]. Regarding the extraction of these compounds, the great majority of the applications consist of a concentration step using low temperatures followed by precipitation with a variety of organic solvents.…”
Section: Extraction Of Carbohydrates From Microalgaementioning
confidence: 99%
“…Nevertheless, little information is available about the classes of polysaccharides present in most microalgal species, with the exception of some β-glucans and spirulans [29,30]. However, microalgal carbohydrates, and mainly their structure and physico-chemical properties, are responsible for the different and important healthpromoting properties such as anti-inflammatory, antitumor, anti-adhesive, antiviral or antibacterial activities [30].…”
Section: Extraction Of Carbohydrates From Microalgaementioning
confidence: 99%
“…Derivatization methods of aminoglycosides have been reviewed before (49). Alditol acetates have been widely used for determination of neutral and basic monosaccharides simultaneously (50-52) however failed in uronic acids detection without forming methyl esters (52). The derivatization procedure including silylation, acetylation, oximation + acetylation and oximation + silylation have been compared for the analysis of iminosugars (DNJ and fagomine) and other low molecular weight carbohydrates.…”
Section: Sugar Acidsmentioning
confidence: 99%
“…Previous studies on the carbohydrate content of algal biomass showed that the two most abundant monomeric sugars present in C. vulgaris are D-galactose and Dglucose (49 wt% and 35 wt% of total carbohydrate respectively). 43 The ACCU-CHEK Performa glucose meter used was responsive to both D-glucose and D-galactose. This is not unusual, for several glucose-meters have been reported to give unusually high readings in the presence of other sugars such as maltose or galactose.…”
Section: Effect Of the Pretreatment On Carbohydratesmentioning
confidence: 99%